Alimentación de corderos con una dieta deficiente en zinc: efecto sobre parámetros relacionados con la absorción y el metabolismo del cobre - Pechin, G.H. (2022)
The objective of this trial was to study the effect of a diet deficient in Zn on Cu plasma levels, tissue concentrations and mineral retention in lambs. Ten lambs were randomly assigned to two groups: basal (B; 10 ppm of Zn) and supplemented with 30 ppm of Zn (Z). The trial lasted for 20 weeks. Blood samples were collected every 4 weeks by jugular venipuncture. In weeks 6 and 20, Cu balance was evaluated. At the end of the trial, euthanasia was performed and samples of muscle, liver, pancreas, testis, kidney, lung, bone and wool were collected to determine the concentration of Cu. Plasma Cu levels were only lower in group Z in the last sampling. In the first balance period, the apparent digestibility of Cu was lower in group Z (46.78 %) than in group B (52.76 %), while Cu retention had a similar trend. However, in the second balance period, no differences were detected between the groups. The Cu concentration in liver and wool was lower in group Z. The rest of the variables did not differ between treatments. These results suggest that zinc deficiency increases Cu absorption and its concentration in liver and wool.